2014
DOI: 10.1587/transinf.2014edl8079
|View full text |Cite
|
Sign up to set email alerts
|

Completely Independent Spanning Trees on Some Interconnection Networks

Abstract: SUMMARYLet T 1 , T 2 , . . . , T k be spanning trees in a graph G. If, for any two vertices u, v of G, the paths joining u and v on the k trees are mutually vertex-disjoint, then T 1 , T 2 , . . . , T k are called completely independent spanning trees (CISTs for short) of G. The construction of CISTs can be applied in fault-tolerant broadcasting and secure message distribution on interconnection networks. Hasunuma (2001) first introduced the concept of CISTs and conjectured that there are k CISTs in any 2k-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…For constructing two CISTs, the results in [5], [13], [14], [23] are based on Theorem 1, and the results in [2], [21] are based on Theorem 2. In this paper, we apply Theorem 1 to construct two CISTs of balanced hypercubes.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…For constructing two CISTs, the results in [5], [13], [14], [23] are based on Theorem 1, and the results in [2], [21] are based on Theorem 2. In this paper, we apply Theorem 1 to construct two CISTs of balanced hypercubes.…”
Section: Preliminariesmentioning
confidence: 99%
“…Accordingly, researches investigating sufficient conditions for graphs that admit multiple CISTs, such as degree-based conditions, can be found in [1], [3], [7], [15], [17]. Also, with the help of constructions, it has been confirmed that certain classes of graphs possess two CISTs, e.g., 4-connected maximal planar graphs [13], Cartesian product of any 2-connected graphs [14], 4-regular chordal rings [2], [23], crossed cubes [5], and several hypercube-variant networks [21]. In addition, more graphs possessing multiple CISTs can be found in [6], [12], [16], [19], [20], [22].…”
Section: Introductionmentioning
confidence: 97%
“…, 00001(2), 00010(3), 00011(4), 00100(5), 00101 (6), 00110 (7), 00111 (8), 01000 (9), 01001 (10), 01010 (11), 01011 (12), 01100 (13), 01101 (14), 01110 (15), 01111 (16), 10000 (17), 10001 (18), 10010 (19) 18) 11000( 25) 10000( 17) 00000 (1) 01111( 16) 01100( 13) 01101( 14) 01110( 15) 00010( 3) 00001( 2) 00100( 5) 10100( 21) 11011( 28) 00011( 4) 01011( 12) 00110( 7) 00101( 6) 00111( 8) 01001( 10 18) 00110( 7) 10100( 21) 10000 (17) 10011( 20) 11011( 28) 01001 (10) 01110( 15) 01000( 9) 01010( 11) 00001( 2) 00101( 6) 00010( 3) 00011( 4) 01011( 12) 01100( 13) 00000( 1) 11100( 29) 00111( 8) 00100…”
Section: P P P P Sunclassified
“…He showed that there exists a k−connected graph which does not contain two CISTs for each k ≥ 2. Pai et al [14] showed that the results are negative to Hasunuma's conjecture in case of hypercube of dimension n ∈ {10, 12, 14, 20, 22, 24, 26, 28, 30}. Many authors provided a necessary condition of CISTs [1,2,5,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…He also posted a conjecture that there exist k CISTs in a 2k-connected graph. Currently, this conjecture has been proved to fail by counterexamples [23], [28]. For recent research results on CISTs and their applications, the reader can refer to [24]- [27] and references quoted therein.…”
Section: Introductionmentioning
confidence: 99%